Analisis Pengaruh Daya Tanggap, Suasana Toko, dan Promosi terhadap Kepuasan Pelanggan pada Noerani Coffee Medan Timur - Maceru Edwardo Hutagaol; Rangga Restu Prayogo (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
The coffee shop industry in Indonesia is growing rapidly along with changes in people's lifestyles that make coffee shops not just a place to enjoy coffee, but also a space to socialize, work, and support a modern lifestyle. Increasingly competitive competition requires every business actor, including Noerani Coffee, East Medan, to be able to provide customer satisfaction by improving service quality, store atmosphere, and appropriate promotional strategies. The problematic phenomenon found at Noerani Coffee is the persistence of customer complaints related to unresponsive service, a less than optimal atmosphere, and limited promotions. This study aims to analyze the influence of responsiveness, store atmosphere, and promotions on customer satisfaction at Noerani Coffee, East Medan. The study used a quantitative approach with a purposive sampling technique, involving 169 Noerani Coffee customer respondents. Data were collected through questionnaires, tested with validity and reliability tests, and analyzed using multiple linear regression analysis methods through the SPSS 26.0 program. The results showed that responsiveness had a positive and significant effect on customer satisfaction, store atmosphere had a positive and significant effect, and promotions also had a positive and significant effect. Simultaneously, the three independent variables have a significant effect on customer satisfaction with an R-Square value of 0.784, which means that 78.4% of the variation in customer satisfaction is explained by responsiveness, store atmosphere, and promotion, while the remaining 21.6% is influenced by other factors outside the study. In conclusion, increasing the speed and responsiveness of service, creating a comfortable coffee shop atmosphere, and effective promotions have been proven to be able to increase customer satisfaction. This study is expected to be a strategic input for Noerani Coffee in strengthening its competitiveness through excellent service, a supportive store atmosphere, and targeted promotions, so that it can maintain customer loyalty amidst increasingly tight competition in the coffee shop industry.